Antimicrobial activity of red dragon fruit peel extract against Staphylococcus aureus for root canal irrigation - Daryono, Daryono; Purba, Member Reni; Al-Furqa'an, Muhammad (Fakultas Kedokteran, Kedokteran Gigi, dan Ilmu Kesehatan, 2025)
Staphylococcus aureus is a type of bacteria that can colonise root canals, leading to infection and pain. Root canal irrigants are substances used during root canal treatment, and sodium hypochlorite is the gold standard, despite its toxicity. Red dragon fruit peel has several active compounds with antibacterial properties. This study aimed to determine the effectiveness of red dragon fruit peel extract (Hylocereus polyrhizus) against S. aureus as a root canal irrigant. This was an experimental study with a post-test-only group design. The study population was pure S. aureus. The study consisted of five treatment groups: red dragon fruit peel extract at concentrations of 80%, 40%, and 20%, 0.2% chlorhexidine, and DMSO, with five repetitions. Antibacterial effectiveness was tested using the disc diffusion method. Data were analysed using the Kruskal-Wallis statistical test and Post Hoc LSD. The study results showed average inhibition zone diameters of red dragon fruit peel extract against S. aureus of 12.18±0.228 mm, 11.16±0.305 mm, and 9.54±0.603 mm for concentrations of 80%, 40%, and 20%, respectively. The highest average inhibition zone diameter was found in the positive control (0.2% chlorhexidine), which was 13.20±0.255 mm, while the negative control (DMSO) showed no inhibition against S. aureus. The Kruskal-Wallis test results indicated that there was a significant effect of red dragon fruit peel extract against S. aureus (p=0.0001; p<0.05). The Post Hoc LSD test results showed that there were differences in the effectiveness of red dragon fruit peel extract between the two different groups (p=0.0001; p<0.05). Red dragon fruit peel extract can be used as a root canal irrigant, with a concentration of 80% being the most effective concentration.